SERS-based CRISPR/Cas assay on microfluidic paper analytical devices for supersensitive detection of pathogenic bacteria in foods - Zhuang, Jianwen; Zhao, Zhiying; Lian, Kai; Yin, Lijuan; Wang, Jiajing; Man, Shuli; Liu, Guozhen; Ma, Long (Biosensors & bioelectronics, 2022)
Rapid and point-of-need (PON) detection of bacteria is crucial to directly provide rapid and reliable diagnostics information during on-site tests, allowing more room for taking proactive measures. By taking the multifaceted advantages of CRISPR/Cas12a and surface-enhanced Raman scattering (SERS), for the first time, we designed a recombinase polymerase amplification (RPA)-integrated microfluidic paper-based analytical device (μPAD), coined RPA-Cas12a-μPAD for supersensitive SERS detection. Single-stranded DNAs were designed to “pull down” SERS nanoprobes. The amplicons of the invA gene triggered the trans-cleavage of Cas12a, resulting in the indiscriminate shredding of linker ssDNA. Thus, the degree of aggregation of SERS nanoprobes was dependent on the concentration of Salmonella typhimurium (S. typhi), which was determined on a μPAD and monitored by a Raman spectrometer. The limit of detection for S. typhi was approximately 3–4 CFU/mL for spiked milk and meat samples with a dynamic detection range from 1 to 108 CFU/mL. The RPA-Cas12a-μPAD secured accurate tests for food samples in 45 min. This work expands the reach of CRISPR-based diagnostics (CRISPR-Dx) and provides a novel and robust bacterial PON detection platform. [Display omitted] •For the first time, a recombinase polymerase amplification-integrated microfluidic paper-based analytical device (μPAD) was fabricated for SERS detection of pathogenic bacteria.•It was able to supersensitive, specific and quantitative detection of Salmonella typhimurium in less than 45 min.•It was capable of Salmonella typhimurium detection in real food samples, which was comparable or better than the most reported methods.